ASSOCIATIONS OF CENOZOIC BASALTIC ROCKS IN THE SEA OF JAPAN - S'yedin V.T. (My University, 1987)
This article describes Cenozoic basaltic rocks in the Sea of Japan. Analysis of a large body of data leads to a division of them into natural associations of volcanic rocks and specific geochemical types. Their classification is based on the chemical properties of these rocks and their minerals, taking into account the mode of evolution of the parental basalt magma, and on their relationship to different morphostructures in the Sea of Japan. There are four associations of Cenozoic basaltic rocks here: 1) continental tholeiites; 2) island-arc volcanics; 3) basaltic rocks of marginal seas, i.e., tholeiites and related differentiates; 4) alkalic basaltic volcanics of the type characteristic of continental rifts.
Keywords: Cenozoic; Cenozoic; Кайнозой